Black Hills [compact disc, unabridged] - Roberts, Nora (Brilliance Audio, 2009)
A summer at his grandparents' South Dakota ranch is not eleven-year-old Cooper Sullivan's idea of a good time. But things are a bit more bearable now that he's discovered the neighbor girl, Lil Chance, and her homemade batting cage. Even horseback riding isn't as awful as Coop thought it would be. Each year, their friendship deepens from innocent games to stolen kisses, but there is one shared experience that will forever haunt them: the terrifying discovery of a hiker's body.